Studies on Electronic Effects on the Singlet-Triplet Gap of Aryl-C4H3Si - Vessally, E.; Khani, A.; Edjlali, L.; Nikoorazm, M. (Asian Journal of Chemistry, 2013)
The thermal energies (E), enthalpies (H) and Gibbs free energies (G) and their gap energies between singlet (s) and triplet (t) states including DEs-t, DHs-t and DGs-t of Ar-C4H3Si (G = -NH2, -OH, -CH3, -F, -Cl, -Br, -H, -CF3 and -NO2) were studied at B3LYP/6-311++G** level of theory.